2010
DOI: 10.1016/j.jchromb.2010.08.039
|View full text |Cite
|
Sign up to set email alerts
|

A liquid chromatography–tandem mass spectrometric method for quantification of curcuminoids in cell medium and mouse plasma

Abstract: Curcumin and tetrahydrocurcumin (THC) have been found as potent DNMT1 inhibitors, but they suffer from low oral bioavailability and rapid metabolism in vivo. To circumvent these problems, two curcumin analogs: 1,7-bis(3,4-dimethoxyphenyl)-4,4-dimethyl-1,6-heptadiene-3,5-dione (TMC) and 1,7-bis(3,4-dimethoxyphenyl)-4-cyclohexyl-1,6-heptadiene-3,5-dione (DMCHC) have been synthesized to enhance their stability by blocking the two metabolic sites, the phenolic and C4 methylene moieties. Both compounds have shown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 23 publications
2
38
1
Order By: Relevance
“…We have reported two LC-MS/MS methods for the quantitation of curcumin, THC, TMC, and DMCHC [9] and the quantitation of curcumin and COG [10]. Therefore, we first evaluated the same extraction and LC conditions for these curcuminoids and curcumin metabolites under the negative mode defined from Section 3.1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have reported two LC-MS/MS methods for the quantitation of curcumin, THC, TMC, and DMCHC [9] and the quantitation of curcumin and COG [10]. Therefore, we first evaluated the same extraction and LC conditions for these curcuminoids and curcumin metabolites under the negative mode defined from Section 3.1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we characterized the mass spectra of curcumin, its two synthetic analogs tetramethyl curcumin (TMC) and dimethylcyclohexyl curcumin (DMCHC), and its two metabolites tetrahydrocurcumin (THC) and curcumin O -glucuronide (COG) under a positive ion mode on a Thermo TSQ Quantum triple quadrupole mass spectrometer [9,10]. The protonated molecular ions are the predominant ions in their respective mass spectra; the major fragmentation pathway for curcumin, THC, TMC, and DMCHC is the cleavage of the heptenoid chain between the 3rd and the 4th carbon atoms (Scheme 1) [9]; and the major fragmentation for COG is glycosidic cleavage (Scheme 1) [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation half lives of curcumin, and THC were 186 and 813 min respectively in cell culture medium. In plasma, their respective half-lives were 111 and 232 min [81]. It has been also reported that THC and curcumin increased Epigallocatechin-3-gallate uptake by greater than two-fold in MDCKII/MRP1 and HT-29 cells [82].…”
Section: Bioavailability Of Curcumin and Thcmentioning
confidence: 86%